MODERASI GENDER DALAM HUBUNGAN KUALITAS LAYANAN DAN KEPUASAN NASABAH: STUDI KASUS CUSTOMER SERVICE BANK BRI DI INDONESIA - SOFYAN, MOHAMMAD; RUMIKI, DJURAIDJ; MUSADAT, IRFAN ACHMAD; NURHIDAYATI, NININ (JURNAL AKUNTANSI DAN KEUANGAN, 2024)
This study aims to analyze the impact of service quality dimensions on customer satisfaction at Bank BRI, focusing on five dimensions of service quality: Tangibles, Empathy, Responsiveness, Reliability, and Assurance. The study uses a quantitative method with data analysis employing Partial Least Squares Structural Equation Modeling (PLS-SEM) and involves 140 Bank BRI customer respondents from across Indonesia. The results indicate that the dimensions of Assurance, Tangibles, Reliability, Responsiveness, and Empathy significantly affect customer satisfaction. This study also examines the moderating role of customer service gender in the relationship between service quality dimensions and customer satisfaction, which shows a small effect with an f² value of 0.009, indicating that gender does not significantly impact this relationship. Based on these findings, it is recommended that Bank BRI improve service quality by focusing on physical elements and customer service competencies, as well as enhancing the Empathy dimension to increase overall customer satisfaction. This study provides important insights for bank management in efforts to enhance customer satisfaction and loyalty through improved service quality.